Comparative Analysis of AlN Thin Film Uniformity on 2-Inch and 4-Inch Si Wafers Prepared by Magnetron Sputtering - Azman, Zulkifli; Mohammad Shuhaili, Falah Abid; Abu Bakar, Ahmad Shuhaimi; Mat Husin, Mohd Rofei; Khan, Jahanzeb; Nayan, Nafarizal (International Journal of Integrated Engineering, 2025)
Aluminium nitride (AlN) is one of most investigated III-V materials for advanced electronics application. This study is a comparative analysis on the AlN thin film deposited on 2-inch and 4-inch Si wafers using radiofrequency (RF) magnetron sputtering. This study investigates the uniformity of AlN thin films deposited on 2-inch and 4-inch Si wafers, analysing variations in crystal structure, surface morphology, and film thickness to assess the impact of wafer size on film consistency. The deposited AlN thin films were characterized using X-ray Diffraction (XRD), surface profiling and field emission – scanning electron microscope (FE-SEM). It was found out that the films had a preferred orientation of (100) and had a very good match across the 2-inch wafers but were off slightly at the edges of the 4-inch wafers. Thickness measurements also showed good uniformity as evidenced by coefficient of variation (CV) values below the 10% industry standard and FE-SEM analysis of smooth, defect-free films with uniform morphology. In conclusion, these results confirm that the wafer size is very crucial to produce uniform ad high quality AlN thin films across the wafer.